Application of Constructivist Language Learning Theory in Learning the Indonesian Language at Muhammadiyah 2 Vocational School Palembang - Houtman, Houtman; Maulini, Suciarti; Mawarti, Arfiah Ayudian; Monalisa, Monalisa; Aprianitasari, Seli (Lentera: Jurnal Ilmiah Kependidikan, 2023)
This research aims to find out how constructivist learning theory is applied in Indonesian language learning at the secondary school level, namely at SMK Muhammadiyah 2 Palembang. The research method used in this research is qualitative. The results of the research show that there are six stages in the learning process using a constructivist theory approach which includes: (1) listening, (2) expressing opinions, (3) dividing into groups, (4) giving assignments, (5) discussing in groups, and (6) evaluate the text of the saga in the form of a video that has been watched together. Based on the results of the research that has been carried out, it was found that the application of constructivist language learning theory has relevance to the learning outcomes of saga texts in the form of listening elements. Students can evaluate and create information in the form of ideas, thoughts, feelings, views, directions, or accurate messages from listening to the text. the story in the form of a video that has been presented. So that students can learn independently and critically through various learning activities.